SOSIALISASI TAHAPAN PENYUSUNAN RENCANA ANGGARAN BIAYA DAN PENJADWALAN PROYEK KONSTRUKSI - Thioritz, Stevy; Gabriella Tecoalu, Gladys (Gapenas Publisher, 2024)
Budget plan and implementation schedule are certainly important parts of project management. Constraints in preparing budget plan and implementation schedule will cause other constraints, for example in the bargaining process it will be difficult to reach a deal price if there is no specific price reference that is right and there can also be a unenough budget in the future. Therefore, socialization in the form of short course to foremen, construction workers need to be given so that they can know or refresh their knowledge about the stages of making a Cost Budget Plan and Scheduling. Foremen also get new ways or tips through the presentation of the stages of making a Cost Budget Plan and Scheduling and expect further guidance on the constraints they encounter later. Making a Cost Budget Plan and Scheduling in project implementation, both on a small and large scale, is a reference in negotiating and controlling project costs and time, and the need for basic knowledge about determining the dimensions of structural elements of the building before calculating the work volume.